2010
DOI: 10.1111/j.1365-2958.2010.07323.x
|View full text |Cite
|
Sign up to set email alerts
|

A structural model of anti‐anti‐σ inhibition by a two‐component receiver domain: the PhyR stress response regulator

Abstract: SummaryPhyR is a hybrid stress regulator conserved in a-proteobacteria that contains an N-terminal s-like (SL) domain and a C-terminal receiver domain. Phosphorylation of the receiver domain is known to promote binding of the SL domain to an anti-s factor. PhyR thus functions as an anti-anti-s factor in its phosphorylated state. We present genetic evidence that Caulobacter crescentus PhyR is a phosphorylation-dependent stress regulator that functions in the same pathway as s T and its anti-s factor, NepR. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 70 publications
4
87
1
1
Order By: Relevance
“…Superimposition of the individual subdomains σ 2 and σ 4 of PhyR SL with the corresponding regions of a prototypical ECF sigma factor, σ E [Protein Data Bank (PDB) ID code 1OR7] (28) showed that the PhyR SL subdomains essentially retain the typical fold of ECF sigma factors, with rmsds of 3.12 Å and 0.80 Å, respectively (Fig. S2), except for helix α4 of bona fide ECF sigma factors, which is absent in PhyR orthologs (16) (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Superimposition of the individual subdomains σ 2 and σ 4 of PhyR SL with the corresponding regions of a prototypical ECF sigma factor, σ E [Protein Data Bank (PDB) ID code 1OR7] (28) showed that the PhyR SL subdomains essentially retain the typical fold of ECF sigma factors, with rmsds of 3.12 Å and 0.80 Å, respectively (Fig. S2), except for helix α4 of bona fide ECF sigma factors, which is absent in PhyR orthologs (16) (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…3A). Whereas the σ 2 -σ 4 linker was described as a dynamic hinge in unphosphorylated PhyR (16), it undergoes an outward movement and positions helix α4 to allow its participation in NepR helix α1′ recognition in the complex. In the PhyR SL -NepR complex, the position of helix α4 is not compatible with the position of the receiver domain in unphosphorylated PhyR and generates a steric clash with α12 (Fig.…”
Section: Structural Comparison Between the Phyr Sl -Nepr Complex Andmentioning
confidence: 99%
See 2 more Smart Citations
“…As is the case for other response regulators, the activity of PhyR is controlled by phosphorylation of a conserved Asp residue in its REC domain. Despite a rather advanced understanding of the partner switch itself (15)(16)(17), little is known about the decisive step of GSR activation, that is, regulation of PhyR phosphorylation. As a response regulator, PhyR is expected to be part of a two-component system, or phosphorelay, working together with one or several histidine kinases that control PhyR phosphorylation upon sensing a particular stimulus.…”
mentioning
confidence: 99%